(3TQM GdTQMs - (3eLghds ((3eMeO TajY TgQjGQjs)
(3ChdgG (B:s
(3JhLgfG Edi LfGH bOSc (B... (3gPG ENhGfj cdGej aj TQM GdTQM HQqjG Yf GdfbU SdjeG Yf GdLQM Ydi hab edJeSce hehLH ebJQMce hCQJH ajg Hjf GdTQMjf hCNQLJ GddBdjA Hjf GdUOajf hChMjJ GdfeHGMK ef GdWQajf(B...s
(3BNQgG (B:s
... (3hdG jfJaY Hg EdG Ph OQHI (B.. (3GdeHGMKGJ hacQg eJYdb aj GdeHGOF MJi jfJgj Edi GdZGjGJ (B... (3agh HgPG GdcJGH ChLH hGdfgj Yf GUGYJg Edi GdMGedjf hGdeJadSajf Chdi hChLH (B.s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs